Decreased sarcoplasmic reticulum phospholipids in human skeletal muscle are associated with metabolic syndrome - Adamson, Samantha E.; Adak, Sangeeta; Petersen, Max C.; Higgins, Dustin; Spears, Larry D.; Zhang, Rong Mei; Cedeno, Andrea; McKee, Alexis; Kumar, Aswathi; Singh, Sudhir; Hsu, Fong-Fu; McGill, Janet B.; et al. (Journal of lipid research, 2024)
Metabolic syndrome affects more than one in three adults and is associated with increased risk of diabetes, cardiovascular disease, and all-cause mortality. Muscle insulin resistance is a major contributor to the development of the metabolic syndrome. Studies in mice have linked skeletal muscle sarcoplasmic reticulum (SR) phospholipid composition to sarcoplasmic/endoplasmic reticulum Ca2+-ATPase activity and insulin sensitivity. To determine if the presence of metabolic syndrome alters specific phosphatidylcholine (PC) and phosphatidylethanolamine (PE) species in human SR, we compared SR phospholipid composition in skeletal muscle from sedentary subjects with metabolic syndrome and sedentary control subjects without metabolic syndrome. Both total PC and total PE were significantly decreased in skeletal muscle SR of sedentary metabolic syndrome patients compared with sedentary controls, particularly in female participants, but there was no difference in the PC:PE ratio between groups. Total SR PC levels, but not total SR PE levels or PC:PE ratio, were significantly negatively correlated with BMI, waist circumference, total fat, visceral adipose tissue, triglycerides, fasting insulin, and homeostatic model assessment for insulin resistance. These findings are consistent with the existence of a relationship between skeletal muscle SR PC content and insulin resistance in humans.